PEMODELAN KEBIJAKAN KEUANGAN DENGAN PENDEKATAN SISTEM DINAMIK DI PROVINSI GORONTALO - Irfan Ibrahim (Publik : (Jurnal Ilmu Administrasi), 2015)
The research intend to obtain get the illustration of structure and behavior of monetary model at Gorontalo Province, and to get result of simulation which relative effective rather than several policy alternative to be taken by Government of Gorontalo Province in order to decreased the dependence to Central Government. The approaching that used to analyse this problem that is “system dynamics” approach, with simulation experiment that illustration the monetary local ability of Gorontalo Province. Simulation result showed that if available of general allocation fund unlimited, therefore Local Government always pursue growth goals, but will happened which running wide between fiscal capacities with fiscal requirement. It means the growth which happened really support by counter balance fund. Plant tax scenario equal to 20 % by the year and scenario income of BUMD equal to 20 % and 30 % by the year in fact unable to do much in lessening fiscal differences. When scenario growth of retribution and tax improved to become 30 % and conducted fusion scenario, in the reality can lessen fiscal difference and on a long term can improve monetary ability of Gorontalo Province. Beside that growth of economics that happened quiet better than the growth in other scenario.